Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 206549 by Shrodinger last updated on 18/Apr/24

∫_0 ^(+∞) (e^(−x^2 ) /((x^2 +(1/2))^2 ))dx

0+ex2(x2+12)2dx

Commented by Frix last updated on 18/Apr/24

(√π)

π

Commented by Shrodinger last updated on 18/Apr/24

how please ?

howplease?

Answered by Frix last updated on 18/Apr/24

∫_0 ^∞ (e^(−x^2 ) /((x^2 +(1/2))^2 ))dx=2∫_0 ^∞ e^(−x^2 ) (1−((x^4 +x^2 −(1/4))/((x^2 +(1/2))^2 )))dx=  =2∫_0 ^∞ e^(−x^2 ) dx−2∫_0 ^∞ e^(−x^2 ) ((x^4 +x^2 −(1/4))/((x^2 +(1/2))^2 ))dx  2∫_0 ^∞ e^(−x^2 ) dx=(√π)  −2∫_0 ^∞ e^(−x^2 ) ((x^4 +x^2 −(1/4))/((x^2 +(1/2))^2 ))dx=[((xe^(−x^2 ) )/(x^2 +(1/2)))]_0 ^∞ =0

0ex2(x2+12)2dx=20ex2(1x4+x214(x2+12)2)dx==20ex2dx20ex2x4+x214(x2+12)2dx20ex2dx=π20ex2x4+x214(x2+12)2dx=[xex2x2+12]0=0

Answered by Berbere last updated on 18/Apr/24

∫_0 ^∞ (e^(−tx^2 ) /(x^2 +a))dx=f(t);f(0)=∫_0 ^∞ (dx/(x^2 +a))=(1/( (√a))).(π/2)  f′(t)=∫_0 ^∞ ((−x^2 )/(x^2 +a))e^(−tx^2 ) dx=−∫_0 ^∞ e^(−tx^2 ) dx+af(t)  f′(t)=−(1/2)(√(π/t))+af(t)  f(t)=ke^(at) ⇒k′=−(1/2)(√(π/t))e^(−at) .⇒k=−(√π)∫(e^(−at) /(2 (√t)))dt;t=x^2   =−(√π)∫e^(−ax^2 ) dx=^(y=x(√a)) −(π/( 2)).(1/( (√a)))erf(x(√a))=−(√((2π)/a))erf((√(at)))+c  f(t)=(−(π/( 2(√a)))erf((√(at)))+(π/(2(√a))))e^(at) =(π/(2(√a)))(1−erf((√(at))))e^(at)   =(π/(2(√a)))erfc((√(at)))e^(at)   (∂f/∂a)=−∫_0 ^∞ (1/((x^2 +a)^2 ))e^(−tx^2 ) ∣_((t=1,a=(1/2))) =−A  −(∂f/∂a)(1,(1/2))=−(∂/∂a)(π/(2(√a)))erfc((√a))e^a ∣_(a=(1/2))   =−[−(π/(4a(√a)))erfc((√a))e^a +(π/(2(√a)))(−(1/( (√(aπ))))e^(−a) e^a +erfc((√a))e^a ).]  (π/(2(√(1/2))))erfc((√(1/2)))−(π/( (√2)))(−((√2)/( (√π)))+erc((1/( (√2))))e^(1/2) )=(√π)  ∫_0 ^∞ (e^(−x^2 ) /((x^2 +(1/2))^2 ))=(√π)

0etx2x2+adx=f(t);f(0)=0dxx2+a=1a.π2f(t)=0x2x2+aetx2dx=0etx2dx+af(t)f(t)=12πt+af(t)f(t)=keatk=12πteat.k=πeat2tdt;t=x2=πeax2dx=y=xaπ2.1aerf(xa)=2πaerf(at)+cf(t)=(π2aerf(at)+π2a)eat=π2a(1erf(at))eat=π2aerfc(at)eatfa=01(x2+a)2etx2(t=1,a=12)=Afa(1,12)=aπ2aerfc(a)eaa=12=[π4aaerfc(a)ea+π2a(1aπeaea+erfc(a)ea).]π212erfc(12)π2(2π+erc(12)e12)=π0ex2(x2+12)2=π

Terms of Service

Privacy Policy

Contact: info@tinkutara.com